1975
DOI: 10.1172/jci108142
|View full text |Cite
|
Sign up to set email alerts
|

Glycopeptide storage in skin fibroblasts cultured from a patient with alpha-mannosidase deficiency.

Abstract: A B S T R A C T Patients with mannosidosis, an inherited deficiency of lysosomal a-mannosidase, accumulate large amounts of mannose-rich oligosaccharides (the "core" of the carbohydrate units of many glycoproteins) in brain and liver and excrete these partial degradation products in their urine. A profound a-mannosidase deficiency was demonstrated in fibroblasts cultured from a skin biopsy obtained from a child with mannosidosis. Further, abnormal glycopeptides rich in mannose and similar to oligosaccharides f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1976
1976
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Biochemical studies have demonstrated an accumulation of man nose-rich oligosaccharides in tissues of affected individuals and a generalized deficiency of acidic a-mannosidase activity (1,2,(6)(7)(8). Three major forms of a-mannosidase activity have been described and partially characterized in normal human liver (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical studies have demonstrated an accumulation of man nose-rich oligosaccharides in tissues of affected individuals and a generalized deficiency of acidic a-mannosidase activity (1,2,(6)(7)(8). Three major forms of a-mannosidase activity have been described and partially characterized in normal human liver (9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%